Technology in managing an academic institution with a focus on language faculty - Mat Daud, Nuraihan (IDOSI Publications, 2014)
The presence of technology has an impact on the corporate culture of a university. The academic community has to learn to adapt and adopt the various technologies which include Managed Learning Environment (MLE), Student Learning Environment (SMS) and Learning Management System (LMS) to keep abreast with the latest development in education. The technology that exists has to be managed to obtain the expected return on investment (ROI). This paper presents the initiatives taken by a Malaysian public university in planning and delivering technology services to meet its educational objectives. It discusses factors that are involved which include policy implementation, governance, integration in teaching and learning, learning management system, research and publication. The paper touches on the use of dedicated and open source systems/software in administration, teaching and learning.